2015
DOI: 10.1148/radiol.14141420
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of Tip-embedded Inferior Vena Cava Filters by Using the Endobronchial Forceps Technique: Experience at a Single Institution

Abstract: The endobronchial forceps technique can be safely used to remove tip-embedded IVC filters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 30 publications
1
57
0
Order By: Relevance
“…Avery et al further suggested that dissection using an endobronchial forceps for filter retrieval could be less costly and more effective and might also be used for standard filter removals (24). However Stavropoulos described this technique as fairly aggressive and noted that with excessive traction fractured filter components may embolize to the cardiac chambers and or pulmonary arteries thereby requiring aggressive foreign body retrieval and potentially even necessitating surgical removal (22)(23)(24).…”
Section: Dissection Techniques Endobronchial Forceps Dissection and Rmentioning
confidence: 99%
“…Avery et al further suggested that dissection using an endobronchial forceps for filter retrieval could be less costly and more effective and might also be used for standard filter removals (24). However Stavropoulos described this technique as fairly aggressive and noted that with excessive traction fractured filter components may embolize to the cardiac chambers and or pulmonary arteries thereby requiring aggressive foreign body retrieval and potentially even necessitating surgical removal (22)(23)(24).…”
Section: Dissection Techniques Endobronchial Forceps Dissection and Rmentioning
confidence: 99%
“…5 The rigid endobronchial forceps technique also has been used for retrieval of tip-embedded inferior vena cava filters. 6 These endobronchial grasping forceps with crocodile jaw (3 mm shaft diameter, 6 cm length) can easily be introduced into the rigid bronchoscope or 14 Fr sheath and are perfect for foreign body retrieval such as endobronchial stent, endovascular stent and inferior vena cava filter.…”
Section: Discussionmentioning
confidence: 99%
“…Endovascular dissection to directly release an embedded hook or penetrating strut with bronchoscopy forceps has also been described as a last-ditch effort. 17 These advanced techniques increase the probability of successful retrieval to more than 90% but are also associated with significantly higher complication rates (5.3% vs. 0.4%). 4 Open surgical approaches are yet another possibility but can lead to increased morbidity and prolong hospitalization secondary to the need for laparotomy and caval reconstruction.…”
Section: Introductionmentioning
confidence: 99%